Exploring metapopulation‐scale suppression alternatives for a global invader in a river network experiencing climate change - Healy, Brian D.; Budy, Phaedra; Yackulic, Charles. B.; Murphy, Brendan P.; Schelly, Robert C.; McKinstry, Mark C. (Conservation biology, 2023)
Invasive species can dramatically alter ecosystems, but eradication is difficult, and suppression is expensive once they are established. Uncertainties in the potential for expansion and impacts by an invader can lead to delayed and inadequate suppression, allowing for establishment. Metapopulation viability models can aid in planning strategies to improve responses to invaders and lessen invasive species’ impacts, which may be particularly important under climate change. We used a spatially explicit metapopulation viability model to explore suppression strategies for ecologically damaging invasive brown trout (Salmo trutta), established in the Colorado River and a tributary in Grand Canyon National Park. Our goals were to estimate the effectiveness of strategies targeting different life stages and subpopulations within a metapopulation; quantify the effectiveness of a rapid response to a new invasion relative to delaying action until establishment; and estimate whether future hydrology and temperature regimes related to climate change and reservoir management affect metapopulation viability and alter the optimal management response. Our models included scenarios targeting different life stages with spatially varying intensities of electrofishing, redd destruction, incentivized angler harvest, piscicides, and a weir. Quasi‐extinction (QE) was obtainable only with metapopulation‐wide suppression targeting multiple life stages. Brown trout population growth rates were most sensitive to changes in age 0 and large adult mortality. The duration of suppression needed to reach QE for a large established subpopulation was 12 years compared with 4 with a rapid response to a new invasion. Isolated subpopulations were vulnerable to suppression; however, connected tributary subpopulations enhanced metapopulation persistence by serving as climate refuges. Water shortages driving changes in reservoir storage and subsequent warming would cause brown trout declines, but metapopulation QE was achieved only through refocusing and increasing suppression. Our modeling approach improves understanding of invasive brown trout metapopulation dynamics, which could lead to more focused and effective invasive species suppression strategies and, ultimately, maintenance of populations of endemic fishes. Resumen Las especies invasoras pueden alterar dramáticamente un ecosistema, pero erradicarlas es complicado y suprimirlas es costoso una vez que están establecidas. Las incertidumbres en el potencial de expansión y el impacto de un invasor pueden derivar en una supresión retardada e inadecuada que permite el establecimiento. Los modelos de viabilidad meta poblacional pueden auxiliar en la planeación de estrategias para mejorar las respuestas ante especies invasoras y disminuir su impacto, lo cual puede ser particularmente importante ante el cambio climático. Usamos un modelo meta poblacional espacialmente explícito para explorar las estrategias de supresión usadas con la trucha café (Salmo trutta), una especie invasora y dañina establecida en el Río Colorado en el Parque Nacional del Gran Cañón. Nuestros objetivos fueron estimar la efectividad de las estrategias enfocadas en diferentes etapas de vida y subpoblaciones dentro de una meta población; cuantificar la efectividad de una respuesta rápida ante una nueva invasión en relación a retardar la acción hasta que ocurra el establecimiento; y estimar si los sistemas térmicos e hidrológicos relacionados con el cambio climático y la gestión de cuencas afectarán la viabilidad meta poblacional y alterarán la respuesta óptima de gestión en el futuro. Nuestros modelos incluyeron escenarios enfocados en diferentes etapas de vida con intensidades espacialmente variables de pesca eléctrica, destrucción de redes, cultivo incentivado de pescadores, piscicidas y un dique. La cuasi extinción (CE) sólo se obtuvo con una supresión a nivel meta poblacional enfocada en múltiples etapas de vida. Las tasas de crecimiento poblacional de la trucha fueron más sensibles a los cambios en edad cero y una gran mortalidad adulta. La duración de la supresión requerida para llegar a la CE para una subpoblación grande establecida fue de doce años en comparación con los cuatro de una respuesta rápida a una nueva invasión. Las subpoblaciones aisladas fueron vulnerables a la supresión; sin embargo, las subpoblaciones conectadas por medio de tributarios incrementaron la persistencia meta poblacional al fungir como refugios climáticos. La escasez de agua, cambios impulsores en el almacenamiento de la cuenca y el calentamiento subsecuente causarían declinaciones de la trucha, pero la CE meta poblacional sólo se logró con el reenfoque e incremento de la supresión. Nuestra estrategia de modelado mejora el entendimiento de las dinámicas meta poblacionales de la trucha café invasora, lo cual podría llevar a estrategias de supresión más enfocadas y efectivas y, finalmente, al mantenimiento de las poblaciones de peces endémicos. Exploración de alternativas a la supresión a escala meta poblacional de un invasor mundial en una red de ríos que experimenta el cambio climático 摘要 入侵物种可以极大程度地改变生态系统, 但一旦它们建立种群, 就很难彻底清除, 且控制其种群的费用也十分高昂。入侵物种潜在的扩张和影响存在不确定性, 这可能造成种群控制行动的延迟和不充分, 从而使其得以建立种群。集合种群生存力模型可以帮助战略规划, 以改进对入侵物种的响应, 减少入侵物种的影响, 这一点在气候变化背景下尤为重要。本研究利用一个空间显式的集合种群生存力模型来探究对破坏生态的入侵物种褐鳟鱼(Salmo trutta)的控制策略, 这些褐鳟鱼已在科罗拉多河和大峡谷国家公园的一条支流中建立种群。本研究旨在估计针对集合种群不同生命阶段和亚种群的策略的有效性;量化对新发入侵的快速响应相对于延迟行动至种群建立的有效性;估计与气候变化和水库管理有关的未来水文和温度条件是否会影响集合种群生存力并改变最佳管理响应。我们的模型针对褐鳟鱼不同生命阶段的情景, 包括在空间上进行不同强度的电力捕鱼、破坏鳟鱼产卵区、激励钓鱼者、使用杀鱼剂, 以及建设鱼梁。只有在全流域范围内针对多个生命阶段进行种群控制, 才能实现褐鳟鱼的准灭绝。褐鳟鱼种群增长率对0岁及大型成体死亡率的变化最为敏感。对于一个已建立的大型亚种群, 达到准灭绝所需的控制时间为12年, 而对新发入侵进行快速响应则只需要4年。孤立亚种群容易受到控制;然而, 相互连接的支流亚种群通过作为气候庇护所, 促进了集合种群续存。此外, 水源短缺驱动的水库储量变化及随后的气候变暖会导致褐鳟鱼种群数量下降, 但只有通过重新聚焦并加强种群控制, 才能实现集合种群准灭绝。我们的建模方法增进了对入侵褐鳟鱼集合种群动态的理解, 可以帮助设计更有针对性、更有效的入侵物种控制策略, 最终帮助维持地方特有鱼类的种群。【翻译:胡怡思;审校:聂永刚】